Misconceptions of Project-Based Learning among Indonesian Language Teachers: An Explanatory Sequential Mixed-Methods Study in West Sumatra Senior High Schools - Nita, Olin; Susmita, Nelvia; Fitriani, Eva; Jasrial, Dedi (AL-ISHLAH: Jurnal Pendidikan, 2026)
Many studies have demonstrated the effectiveness of project-based learning (PjBL) in language teaching. However, limited research has examined teachers’ misconceptions during the implementation of this learning model in classroom practice. This present study aims to investigate the levels, types, and parts of PjBL categorized as misconceptions held by Indonesian language teachers in some senior high schools. This explanatory sequential mixed-method design involved 35 teachers who were selected purposively. These teachers taught the Indonesian language subject in some schools in a city in West Sumatra Province, Indonesia. The data were obtained by distributing a set of questionnaires and conducting semi-structured interviews face-to-face. The data were then analyzed quantitatively using descriptive statistics, while the qualitative data were analyzed using the thematic analysis method. The results revealed that many teachers interpreted PjBL as merely assigning project tasks rather than facilitating a structured learning process. Misconceptions were particularly evident in the project planning and reflection stages, where teachers showed limited understanding of how to guide students in inquiry, collaboration, and reflective learning. Interview data further revealed that these misconceptions were related to teachers’ limited conceptual understanding of the core principles and student-centered nature of PjBL. These findings highlight the importance of strengthening teachers’ pedagogical understanding of PjBL and provide empirical insights into how misconceptions may influence the effectiveness of PjBL implementation in language classrooms.